A Computational Analysis of ECC Based Novel Authentication Scheme in VANET - Sachin P. Godse; Parikshit N. Mahalle (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A recent development in the adhoc network is a vehicular network called VANET (Vehicular Adhoc Network). Intelligent Transportation System is the Intelligent application of VANET. Due to open nature of VANET attacker can launch various kind of attack. As VANET messages are deal with very crucial information’s which may save the life of passengers by avoiding accidents, save the time of people on a trip, exchange of secret information etc., because of this security is must be in the VANET. To ensure the highest level of security the network should be free from attackers, there by all information pass among nodes in the network must be reliable i.e. should be originated by an authenticated node. Authentication is the first line of security in VANET; it avoids nonregistered vehicle in the network. Previous research come up with some Cryptographic, Trust based, Id based, Group signature based authentication schemes. A speed of authentication and privacy preservation is important parameters in VANET authentication. This paper addresses the computational analysis of authentication schemes based on ECC. We started analysis from comparing plain ECC with our proposed AECC (Adaptive Elliptic Curve Cryptography) and EECC (Enhanced Elliptic Curve Cryptography). The result of analysis shows proposed schemes improve speed and security of authentication. In AECC key size is adaptive i.e. different sizes of keys are generated during key generation phase. Three ranges are specified for key sizes small, large and medium. In EECC we added an extra parameter during transmission of information from the vehicle to RSU for key generation. Schemes of authentications are evaluated by comparative analysis of time required for authentication and key breaking possibilities of keys used in authentication.